Analysis of the results of psychological and pedagogical research of labor migrants and their families (Middle European Scientific Bulletin, 2021)
This article analyzes the results of a psychological and pedagogical study conducted with labor migrants and their families, including their children, in order to determine the impact of labor migration on family stability in Uzbekistan, and also contains conclusions about the tasks that need to be solved in the context of this problem.